Preparation method of graphite / graphene reinforced magnesium-based composite material with high modulus strength and plasticity matching

By using graphite/graphene hybrid reinforcement in magnesium-based composite materials, and using a double-section backslant blade stirrer and high-dispersed spiral large deformation extrusion technology, the problem that magnesium-based composite materials is difficult to achieve high strength and plasticity under high modulus, and the matching of high modulus, strength and plasticity is achieved.

CN118726789BActive Publication Date: 2025-04-29TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410745303.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-11
Publication Date
2025-04-29
Estimated Expiration
2044-06-11

AI Technical Summary

Technical Problem

Magnesium-based composite materials are difficult to achieve higher strength and plasticity while maintaining high modulus.

Method used

The preparation method of graphite/graphene hybrid reinforced magnesium-based composite material is adopted. By pretreating graphite and graphene, an alternately arranged structural mixed liquid is formed, and the reinforcement is uniformly dispersed in the magnesium-based material through dual-field regulation and ultrasonic treatment. Subsequently, the strength and plasticity of the material are further enhanced by using a special structure of double-section backslant blade agitator and high-dispersed spiral large deformation extrusion technology.

Benefits of technology

The matching of high modulus, strength and plasticity was achieved, with tensile strength ranging from 363.16MPa to 385.26MPa, yield strength ranging from 313.45MPa to 335.35MPa, plasticity ranging from 9.17% to 11.04%, and modulus ranging from 54.8GPa to 56.5GPa.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118726789B_ABST
    Figure CN118726789B_ABST
Patent Text Reader

Abstract

A method for preparing a graphite / graphene reinforced magnesium-based composite material with high modulus, strength and plasticity matching relates to a method for preparing a reinforced magnesium-based composite material. The present invention aims to solve the technical problem that the current magnesium-based composite material has a high modulus but cannot have high strength and plasticity. The two stirring blades of the present invention respectively exert downward pressure and lifting effects on the melt during stirring. During the stirring process, not only does the melt form a vortex in the horizontal direction along the rotation direction, but it can also form a reflux from the center to the outside or from the outside to the center in the longitudinal direction, which can greatly disperse the reinforcement evenly. The present invention uses a self-developed threaded twisted extrusion die to not only further disperse the reinforcement in the matrix during the extrusion process, but also exert three-dimensional compression and strong shear force on the material, so that the reinforcement is highly dispersed and strong plastic deformation occurs, the grains are significantly refined, and finally a graphite / graphene reinforced magnesium-based composite material with high modulus, high strength and high plasticity is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a reinforced magnesium-based composite material. Background Art

[0002] Industries such as aerospace, digital 3C, and weapons require low-density, high-modulus metal materials to save energy and reduce emissions. However, modulus is an inherent property of the material, and only a minimal modulus increment can be obtained through alloying. The elastic modulus of pure magnesium or magnesium alloys can be significantly increased by adding high-modulus metal or non-metal reinforcements. Graphene or carbon nanomaterials are excellent reinforcement materials for magnesium-based composites because they have high strength, high thermal conductivity, and do not react with magnesium at high temperatures. Studies have shown that adding a certain amount of graphene nanosheets (GNPs) to the magnesium matrix significantly improves the yield strength under the premise of a small decrease in plasticity. In addition, studies have shown that adding a second reinforcement to magnesium-based composites reinforced with GNPs can improve the dispersion of GNPs in the magnesium matrix, thereby improving the mechanical properties of the material. GFs and GNPs do not react with each other and have high-temperature stability, strength, and stiffness. In addition, magnesium alloys and composites can be further strengthened by secondary deformation, such as extrusion, rolling, multi-directional forging, and equal channel angular extrusion. However, there are few studies on nanoparticle and glass fiber hybrid reinforced Mg-based composites, especially on hot deformation. Summary of the invention

[0003] The present invention aims to solve the technical problem that the current magnesium-based composite materials have high modulus but cannot have high strength and plasticity, and to provide a method for preparing a graphite / graphene reinforced magnesium-based composite material with high modulus, strength and plasticity matching.

[0004] The preparation method of the high modulus strength plasticity matching graphite / graphene reinforced magnesium-based composite material of the present invention is carried out according to the following steps:

[0005] 1. Pretreatment of graphite and graphene: Put graphite, graphene and zinc powder together in anhydrous ethanol, add an aqueous dispersant, mix and stir for 1h to 1.5h for preliminary microscopic insert treatment, and then perform double-field control on the obtained mixed solution to obtain a structure mixed solution in which graphite, graphene and zinc powder are alternately arranged; then the structure mixed solution in which graphite, graphene and zinc powder are alternately arranged is filtered and dried in turn, and the dried mixed powder is crushed to obtain a graphite / graphene pre-dispersion;

[0006] The ratio of the mass of the aqueous dispersant to the sum of the mass of graphite and graphene is 1:(10-11);

[0007] The mass ratio of graphene, graphite and zinc powder is (7-9):(3-9):(3-9);

[0008] The volume ratio of the sum of the mass of the graphite and graphene to anhydrous ethanol is 10g:(400mL-500mL);

[0009] The dual-field control is to treat the mixed solution with electromagnetic stirring and ultrasound at the same time, the treatment time is 0.5h to 1h, the speed of electromagnetic stirring is 60r / min to 120r / min, and the ultrasound power is 100W to 300W;

[0010] 2. Preparation of graphite / graphene hybrid reinforced magnesium-based composite materials: Put the magnesium alloy ingot into a crucible, introduce a protective atmosphere and heat it to melt it, and remove the waste slag on the surface of the melt after the magnesium alloy is melted; extend a dried double-stage reverse-inclined blade stirrer brushed with talcum powder and zinc oxide paint 1 cm to 2 cm below the liquid surface, and start stirring when the temperature drops to 30°C to 40°C above the liquidus temperature of the magnesium alloy, with a rotation speed of 500rpm to 700rpm. After the melt becomes semi-solid, the preheated step A prepared graphite / graphene pre-dispersion is added at a position close to the stirring shaft, and after all the pre-dispersion is added, the stirring is started for 10 to 20 minutes; the temperature is then raised to 80 to 90° C. above the liquidus line of the magnesium alloy, and then ultrasonic treatment is performed, the ultrasonic power is 1700 W to 2100 W, and the ultrasonic time is 8 to 15 minutes; the melt is then poured into a preheated casting mold, and a load of 360 MPa to 370 MPa is applied to obtain a cast graphite / graphene reinforced magnesium-based composite material;

[0011] The composition of each element in the magnesium alloy ingot is: 3wt.% Zn, 0.1wt.% Y, and the rest is Mg;

[0012] The mass ratio of the graphite / graphene pre-dispersion prepared in step 1 to the liquid magnesium alloy is (2-4):97;

[0013] The protective atmosphere is a mixed gas of CO2 and SF6, and the volume fraction ratio of the two is CO2:SF6=40:(5-6);

[0014] The preheating temperature of the preheating casting mold is 420°C to 430°C;

[0015] The double-stage reverse-oblique blade agitator is composed of a rotating shaft 1, five first stirring blades 2 and five second stirring blades 3; the first stirring blades 2 and the second stirring blades 3 are both rectangular thin-sheet structures, the five first stirring blades 2 are evenly distributed and fixed on the rotating shaft 1, the five first stirring blades 2 are of equal height and are at an angle of 45° to the rotating shaft 1, a second stirring blade 3 is fixed to the outer end of each first stirring blade 2, the first stirring blade 2 and the second stirring blade 3 are in a vertical relationship, a central axis of the first stirring blade 2 coincides with a central axis of the second stirring blade 3, and the five second stirring blades 3 are of equal height and are at an angle of 45° to the rotating shaft 1;

[0016] 3. Large deformation heat treatment of graphite / graphene hybrid reinforced magnesium-based composite materials: Cut the cast graphite / graphene hybrid reinforced magnesium-based composite materials obtained in step 2 into blocks, grind them with a grinder to remove surface oxides, and then wrap them with aluminum foil; use a heat treatment furnace to perform gradient homogenization heat treatment; then heat to 180°C to 210°C and keep warm for 30min to 40min; put them into a mold preheated to 180°C to 210°C, use a four-column vertical pressure testing machine to perform high-dispersion spiral large deformation extrusion, and then air-cool to room temperature to obtain a graphite / graphene reinforced magnesium-based composite material with high modulus, high strength and high plasticity;

[0017] The extrusion ratio during extrusion is (15-16):1, the extrusion temperature is 180°C-210°C, and the extrusion speed is 0.1mm / s-1mm / s;

[0018] The gradient homogenization heat treatment is as follows: first, keep the temperature at 350°C to 360°C for 6h to 6.5h, then heat to 400°C to 410°C and keep the temperature for 14h to 14.5h, and finally perform rapid water cooling;

[0019] The inner cavity of the concave die used for the high-dispersion spiral large-deformation extrusion is a funnel-shaped structure whose opening diameter gradually decreases downward, and a plurality of variable-diameter spiral grooves 4 are evenly arranged on the inner wall of the inner cavity, and each variable-diameter spiral groove 4 becomes thinner from top to bottom.

[0020] In the double-stage reverse-inclined blade stirrer in step 2 of the present invention, the first stirring blade 2 close to the rotating shaft 1 and the second stirring blade 3 far away from the rotating shaft 1 respectively exert downward pressure and lifting effects on the melt during stirring; during the stirring process, not only does the melt form a vortex in the horizontal direction along the rotation direction, but it can also form a reflux from the center to the outside or from the outside to the center in the longitudinal direction, thereby generating multi-directional strong mixing shear forces on the metal melt, which can greatly disperse the reinforcement evenly.

[0021] The inner cavity of the die in step 2 of the present invention is a funnel-shaped structure with an opening that gradually becomes smaller downward, and a plurality of variable-diameter spiral grooves 4 are evenly arranged on the inner wall. During the extrusion process, the material can be subjected to a strong torsional shear force, so that the reinforcement is dispersed more evenly; each variable-diameter spiral groove 4 becomes thinner from top to bottom, which can not only further increase the deformation amount, but also enable the material to smoothly transition to the discharge port, so that the material can be extruded smoothly and evenly.

[0022] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0023] In step 2, the special structure of the self-developed double-stage reverse-inclined blade agitator is used to coordinate the melt in the horizontal and vertical directions during the stirring and dispersing process, and the reinforcement can be greatly dispersed evenly; the special structure of the self-developed double-stage reverse-inclined blade agitator is used to form a vortex in the horizontal direction along the rotation direction during the stirring and dispersing process, and a reflux from the center to the outside or from the outside to the center can be formed in the longitudinal direction; then, the self-developed threaded twisting extrusion die is used, and during the extrusion process, not only can the reinforcement be further dispersed in the matrix, but also three-dimensional compression and strong shear force can be applied to the material, so that the reinforcement is highly dispersed and strong plastic deformation occurs at the same time, and the grains are significantly refined, and finally a high modulus, high strength and high plasticity graphite / graphene reinforced magnesium-based composite material with a tensile strength of 363.16MPa to 385.26MPa, a yield strength of 313.45MPa to 335.35MPa, a plasticity of 9.17% to 11.04%, and a modulus of 54.8GPa to 56.5GPa is obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a three-dimensional schematic diagram of a double-stage reverse-inclined blade agitator in Experiment 1;

[0025] Figure 2 This is a bottom view of the double-stage reverse-inclined blade agitator in Test 1;

[0026] Figure 3 Schematic diagram of the apparatus used for high-dispersion spiral large-deformation extrusion in Experiment 1;

[0027] Figure 4 A top view of the die used for high-dispersion spiral large-deformation extrusion in Experiment 1;

[0028] Figure 5 A cross-sectional view of the concave die used for high-dispersion spiral large-deformation extrusion in Experiment 1;

[0029] Figure 6 This is an optical microstructure diagram of the graphite / graphene reinforced magnesium-based composite material with high modulus, high strength and high plasticity prepared in Experiment 1;

[0030] Figure 7is the optical microstructure of the magnesium alloy material prepared in Experiment 3;

[0031] Figure 8 This is the engineering stress-strain curve. DETAILED DESCRIPTION

[0032] Specific implementation method 1: This implementation method is a method for preparing a graphite / graphene reinforced magnesium-based composite material with high modulus strength and plasticity matching, which is specifically carried out according to the following steps:

[0033] 1. Pretreatment of graphite and graphene: Put graphite, graphene and zinc powder together in anhydrous ethanol, add an aqueous dispersant, mix and stir for 1h to 1.5h for preliminary microscopic insert treatment, and then perform double-field control on the obtained mixed solution to obtain a structure mixed solution in which graphite, graphene and zinc powder are alternately arranged; then the structure mixed solution in which graphite, graphene and zinc powder are alternately arranged is filtered and dried in turn, and the dried mixed powder is crushed to obtain a graphite / graphene pre-dispersion;

[0034] The ratio of the mass of the aqueous dispersant to the sum of the mass of graphite and graphene is 1:(10-11);

[0035] The mass ratio of graphene, graphite and zinc powder is (7-9):(3-9):(3-9);

[0036] The volume ratio of the sum of the mass of the graphite and graphene to anhydrous ethanol is 10g:(400mL-500mL);

[0037] The dual-field control is to treat the mixed solution with electromagnetic stirring and ultrasound at the same time, the treatment time is 0.5h to 1h, the speed of electromagnetic stirring is 60r / min to 120r / min, and the ultrasound power is 100W to 300W;

[0038] 2. Preparation of graphite / graphene hybrid reinforced magnesium-based composite materials: Put the magnesium alloy ingot into a crucible, introduce a protective atmosphere and heat it to melt it, and remove the waste slag on the surface of the melt after the magnesium alloy is melted; extend a dried double-stage reverse-inclined blade stirrer brushed with talcum powder and zinc oxide paint 1 cm to 2 cm below the liquid surface, and start stirring when the temperature drops to 30°C to 40°C above the liquidus temperature of the magnesium alloy, with a rotation speed of 500rpm to 700rpm. After the melt becomes semi-solid, the preheated step A prepared graphite / graphene pre-dispersion is added at a position close to the stirring shaft, and after all the pre-dispersion is added, the stirring is started for 10 to 20 minutes; the temperature is then raised to 80 to 90° C. above the liquidus line of the magnesium alloy, and then ultrasonic treatment is performed, the ultrasonic power is 1700 W to 2100 W, and the ultrasonic time is 8 to 15 minutes; the melt is then poured into a preheated casting mold, and a load of 360 MPa to 370 MPa is applied to obtain a cast graphite / graphene reinforced magnesium-based composite material;

[0039] The composition of each element in the magnesium alloy ingot is: 3wt.% Zn, 0.1wt.% Y, and the rest is Mg;

[0040] The mass ratio of the graphite / graphene pre-dispersion prepared in step 1 to the liquid magnesium alloy is (2-4):97;

[0041] The protective atmosphere is a mixed gas of CO2 and SF6, and the volume fraction ratio of the two is CO2:SF6=40:(5-6);

[0042] The preheating temperature of the preheating casting mold is 420°C to 430°C;

[0043] The double-stage reverse-oblique blade agitator is composed of a rotating shaft 1, five first stirring blades 2 and five second stirring blades 3; the first stirring blades 2 and the second stirring blades 3 are both rectangular thin-sheet structures, the five first stirring blades 2 are evenly distributed and fixed on the rotating shaft 1, the five first stirring blades 2 are of equal height and are at an angle of 45° to the rotating shaft 1, a second stirring blade 3 is fixed to the outer end of each first stirring blade 2, the first stirring blade 2 and the second stirring blade 3 are in a vertical relationship, a central axis of the first stirring blade 2 coincides with a central axis of the second stirring blade 3, and the five second stirring blades 3 are of equal height and are at an angle of 45° to the rotating shaft 1;

[0044] 3. Large deformation heat treatment of graphite / graphene hybrid reinforced magnesium-based composite materials: Cut the cast graphite / graphene hybrid reinforced magnesium-based composite materials obtained in step 2 into blocks, grind them with a grinder to remove surface oxides, and then wrap them with aluminum foil; use a heat treatment furnace to perform gradient homogenization heat treatment; then heat to 180°C to 210°C and keep warm for 30min to 40min; put them into a mold preheated to 180°C to 210°C, use a four-column vertical pressure testing machine to perform high-dispersion spiral large deformation extrusion, and then air-cool to room temperature to obtain a graphite / graphene reinforced magnesium-based composite material with high modulus, high strength and high plasticity;

[0045] The extrusion ratio during extrusion is (15-16):1, the extrusion temperature is 180°C-210°C, and the extrusion speed is 0.1mm / s-1mm / s;

[0046] The gradient homogenization heat treatment is as follows: first, keep the temperature at 350°C to 360°C for 6h to 6.5h, then heat to 400°C to 410°C and keep the temperature for 14h to 14.5h, and finally perform rapid water cooling;

[0047] The inner cavity of the concave die used for the high-dispersion spiral large-deformation extrusion is a funnel-shaped structure whose opening diameter gradually decreases downward, and a plurality of variable-diameter spiral grooves 4 are evenly arranged on the inner wall of the inner cavity, and each variable-diameter spiral groove 4 becomes thinner from top to bottom.

[0048] Specific implementation method 2: This implementation method is different from the specific implementation method 1 in that the drying temperature in step 1 is 80° C. The rest is the same as the specific implementation method 1.

[0049] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that the mass ratio of graphene, graphite and zinc powder in step 1 is 7:3:3. The rest is the same as specific implementation method 1 or 2.

[0050] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that the graphite / graphene predispersion prepared in step 1 is preheated at a temperature of 200° C. and is preheated while wrapped in aluminum foil. Other aspects are the same as those of specific embodiments 1 to 3.

[0051] Specific embodiment 5: This embodiment is different from specific embodiment 4 in that the gradient homogenization heat treatment described in step 3 is: first keep the temperature at 350℃~360℃ for 6h, then increase the temperature to 400℃~410℃ and keep the temperature for 14h, and finally perform rapid water cooling. Others are the same as specific embodiment 4.

[0052] The present invention is verified by the following tests:

[0053] Experiment 1: This experiment is a method for preparing a graphite / graphene reinforced magnesium-based composite material with high modulus strength and plasticity matching, which is specifically carried out in the following steps:

[0054] 1. Pretreatment of graphite and graphene: Put graphite, graphene and zinc powder together in anhydrous ethanol, add an aqueous dispersant, mix and stir for 1 hour for preliminary microscopic insert treatment, and then perform double-field control on the obtained mixed solution to obtain a structure mixed solution in which graphite, graphene and zinc powder are alternately arranged; then the structure mixed solution in which graphite, graphene and zinc powder are alternately arranged is filtered and dried (80°C) in turn, and the dried mixed powder is crushed to obtain a graphite / graphene pre-dispersion;

[0055] The aqueous dispersant is HH2017 from Guangzhou Houhuan Chemical Additive Co., Ltd.

[0056] The ratio of the mass of the aqueous dispersant to the sum of the mass of the graphite and the graphene is 1:10;

[0057] The mass ratio of the graphene, graphite and zinc powder is 1:1:1;

[0058] The volume ratio of the sum of the mass of the graphite and the graphene to the anhydrous ethanol is 1 g:40 mL;

[0059] The dual-field control is to treat the mixed solution with electromagnetic stirring and ultrasound at the same time, the treatment time is 0.5h, the speed of electromagnetic stirring is 100r / min, and the ultrasound power is 200W;

[0060] 2. Preparation of hybrid graphite / graphene reinforced magnesium-based composite materials: Put the magnesium alloy ingot into a crucible, introduce a protective atmosphere and heat it to melt it, and remove the waste slag on the surface of the melt after the magnesium alloy is melted; extend a dried double-stage reverse-inclined blade stirrer brushed with talcum powder and zinc oxide paint 1 cm below the liquid surface, and start stirring when the temperature drops to 30°C above the liquidus temperature of the magnesium alloy, with a rotation speed of 500rpm. After the melt becomes semi-solid, add the preheated graphite / graphene predispersion prepared in step 1 at a position close to the stirring shaft, and start timing stirring for 10 minutes after all the predispersions are added; then heat to 80°C above the liquidus temperature of the magnesium alloy, and then perform ultrasonic treatment with an ultrasonic power of 2000W and an ultrasonic time of 10 minutes; then pour the melt into a preheated casting mold, apply a load of 360MPa, and obtain a cast graphite / graphene reinforced magnesium-based composite material;

[0061] The composition of each element in the magnesium alloy ingot is: 3wt.% Zn, 0.1wt.% Y, and the rest is Mg;

[0062] The mass ratio of the graphite / graphene pre-dispersion prepared in step 1 to the liquid magnesium alloy is 3:97;

[0063] The protective atmosphere is a mixed gas of CO2 and SF6, and the volume fraction ratio of the two is CO2:SF6=8:1;

[0064] The preheating temperature of the preheating casting mold is 420°C;

[0065] like Figure 1 and 2 As shown, the double-stage reverse-oblique blade agitator is composed of a rotating shaft 1, five first stirring blades 2 and five second stirring blades 3; the first stirring blades 2 and the second stirring blades 3 are both rectangular thin-sheet structures, and the five first stirring blades 2 are evenly distributed and fixed on the rotating shaft 1, the five first stirring blades 2 are of equal height and are at an angle of 45° to the rotating shaft 1, a second stirring blade 3 is fixed to the outer end of each first stirring blade 2, the first stirring blade 2 and the second stirring blade 3 are in a vertical relationship, a central axis of the first stirring blade 2 coincides with a central axis of the second stirring blade 3, and the five second stirring blades 3 are of equal height and are at an angle of 45° to the rotating shaft 1;

[0066] 3. Large deformation heat treatment of graphite / graphene hybrid reinforced magnesium-based composite materials: Cut the cast graphite / graphene hybrid reinforced magnesium-based composite materials obtained in step 2 into blocks, grind them with a grinder to remove surface oxides, and then wrap them with aluminum foil; use a heat treatment furnace to perform gradient homogenization heat treatment; then heat to 200°C and keep warm for 30 minutes; put them into a mold preheated to 180°C, use a four-column vertical pressure testing machine to perform high-dispersion spiral large deformation extrusion, and then air-cool to room temperature to obtain a graphite / graphene reinforced magnesium-based composite material with high modulus, high strength and high plasticity;

[0067] The extrusion ratio during extrusion was 15:1, the extrusion temperature was 200°C, and the extrusion speed was 0.5 mm / s;

[0068] The gradient homogenization heat treatment is as follows: first, keep the temperature at 350°C for 6 hours, then heat to 400°C and keep the temperature for 14 hours, and finally perform rapid water cooling;

[0069] like Figure 3 As shown, the device used for the high-dispersion spiral large deformation extrusion is composed of a variable diameter thread extrusion die, a mold, an extrusion block, a cushion block and a pressure head (all devices except the variable diameter thread extrusion die are conventional devices); during extrusion, the variable diameter thread extrusion die, the extrusion block and the cushion block are placed in the mold in sequence, and finally the pressure head is placed on the cushion block, and the press parameters are adjusted to extrude;

[0070] like Figure 4 and Figure 5As shown, the inner cavity of the concave die used for the high-dispersion spiral large deformation extrusion is a funnel-shaped structure with an opening diameter that gradually decreases downward, and a plurality of variable-diameter spiral grooves 4 are evenly arranged on the inner wall of the inner cavity, and each variable-diameter spiral groove 4 becomes thinner from top to bottom.

[0071] Experiment 2: This experiment is different from Experiment 1 in that the mass ratio of graphite, graphene and zinc powder in step 1 is 7:3:3. The rest is the same as Experiment 1.

[0072] Experiment 3: This experiment is a control experiment, and no enhancer is added. The difference from Experiment 1 is that there is no step 1, and the rest is the same as Experiment 1.

[0073] Figure 6 and Figure 7 They are the optical microstructures of the graphite / graphene reinforced magnesium-based composite material with high modulus, high strength and high plasticity prepared in Experiment 1 and the optical microstructures of the magnesium alloy material prepared in Experiment 3. It can be seen from the figures that the recrystallization rate increases due to the introduction of reinforcements, and the grains of the composite material prepared in Experiment 1 are finer than those of the magnesium alloy prepared in Experiment 3; in addition, the reinforcements of the composite material prepared in Experiment 1 are evenly distributed along the extrusion direction.

[0074] The mechanical properties of the materials prepared in Experiments 1, 2 and 3 were tested at room temperature, and the engineering stress-strain curves were obtained, such as Figure 8 As shown, the tensile strength of the composite material prepared in Test 1 is 385.26 MPa, the yield strength is 335.35 MPa, the elongation is 11.04%, and the modulus is 54.8 GPa; the tensile strength of the composite material prepared in Test 2 is 363.16 MPa, the yield strength is 313.45 MPa, the elongation is 9.17%, and the modulus is 56.5 GPa; the tensile strength of the alloy prepared in Test 3 is 316.8 MPa, the yield strength is 300.2 MPa, the elongation is 13.1%, and the modulus is 41.4 GPa.

Claims

1. A method for preparing a graphite / graphene reinforced magnesium-based composite material with high modulus strength and plasticity matching, characterized in that The preparation method of the graphite / graphene reinforced magnesium-based composite material with high modulus strength and plasticity matching is carried out according to the following steps:

1. Pretreatment of graphite and graphene: Put graphite, graphene and zinc powder together in anhydrous ethanol, add an aqueous dispersant, mix and stir for 1h to 1.5h for preliminary microscopic insert treatment, and then perform double-field control on the obtained mixed solution to obtain a structure mixed solution in which graphite, graphene and zinc powder are alternately arranged; then the structure mixed solution in which graphite, graphene and zinc powder are alternately arranged is filtered and dried in turn, and the dried mixed powder is crushed to obtain a graphite / graphene pre-dispersion; The ratio of the mass of the aqueous dispersant to the sum of the mass of graphite and graphene is 1:(10-11); The mass ratio of graphene, graphite and zinc powder is (7-9):(3-9):(3-9); The volume ratio of the sum of the mass of the graphite and graphene to anhydrous ethanol is 10g:(400mL-500mL); The dual-field control is to treat the mixed solution with electromagnetic stirring and ultrasound at the same time, the treatment time is 0.5h to 1h, the speed of electromagnetic stirring is 60r / min to 120r / min, and the ultrasound power is 100W to 300W; 2. Preparation of graphite / graphene hybrid reinforced magnesium-based composite materials: Put the magnesium alloy ingot into a crucible, introduce a protective atmosphere and heat it to melt it, and remove the waste slag on the surface of the melt after the magnesium alloy is melted; extend a dried double-stage reverse-inclined blade stirrer brushed with talcum powder and zinc oxide paint 1 cm to 2 cm below the liquid surface, and start stirring when the temperature drops to 30°C to 40°C above the liquidus temperature of the magnesium alloy, with a rotation speed of 500rpm to 700rpm. After the melt becomes semi-solid, the preheated step A prepared graphite / graphene pre-dispersion is added at a position close to the stirring shaft, and after all the pre-dispersion is added, the stirring is started for 10 to 20 minutes; the temperature is then raised to 80 to 90° C. above the liquidus line of the magnesium alloy, and then ultrasonic treatment is performed, the ultrasonic power is 1700 W to 2100 W, and the ultrasonic time is 8 to 15 minutes; the melt is then poured into a preheated casting mold, and a load of 360 MPa to 370 MPa is applied to obtain a cast graphite / graphene reinforced magnesium-based composite material; The composition of each element in the magnesium alloy ingot is: 3wt.% Zn, 0.1wt.% Y, and the rest is Mg; The mass ratio of the graphite / graphene pre-dispersion prepared in step 1 to the liquid magnesium alloy is (2-4):97; The protective atmosphere is a mixed gas of CO2 and SF6, and the volume fraction ratio of the two is CO2:SF6=40:(5-6); The preheating temperature of the preheating casting mold is 420°C to 430°C; The double-stage reverse-oblique blade agitator is composed of a rotating shaft 1, five first stirring blades 2 and five second stirring blades 3; the first stirring blades 2 and the second stirring blades 3 are both rectangular thin-sheet structures, the five first stirring blades 2 are evenly distributed and fixed on the rotating shaft 1, the five first stirring blades 2 are of equal height and are at an angle of 45° to the rotating shaft 1, a second stirring blade 3 is fixed to the outer end of each first stirring blade 2, the first stirring blade 2 and the second stirring blade 3 are in a vertical relationship, a central axis of the first stirring blade 2 coincides with a central axis of the second stirring blade 3, and the five second stirring blades 3 are of equal height and are at an angle of 45° to the rotating shaft 1; 3. Large deformation heat treatment of graphite / graphene hybrid reinforced magnesium-based composite materials: Cut the cast graphite / graphene hybrid reinforced magnesium-based composite materials obtained in step 2 into blocks, grind them with a grinder to remove surface oxides, and then wrap them with aluminum foil; use a heat treatment furnace to perform gradient homogenization heat treatment; then heat to 180°C to 210°C and keep warm for 30min to 40min; put them into a mold preheated to 180°C to 210°C, use a four-column vertical pressure testing machine to perform high-dispersion spiral large deformation extrusion, and then air-cool to room temperature to obtain a graphite / graphene reinforced magnesium-based composite material with high modulus, high strength and high plasticity; The extrusion ratio during extrusion is (15-16):1, the extrusion temperature is 180°C-210°C, and the extrusion speed is 0.1mm / s-1mm / s; The gradient homogenization heat treatment is as follows: first, keep the temperature at 350°C to 360°C for 6h to 6.5h, then heat to 400°C to 410°C and keep the temperature for 14h to 14.5h, and finally perform rapid water cooling; The inner cavity of the concave die used for the high-dispersion spiral large-deformation extrusion is a funnel-shaped structure whose opening diameter gradually decreases downward, and a plurality of variable-diameter spiral grooves 4 are evenly arranged on the inner wall of the inner cavity, and each variable-diameter spiral groove 4 becomes thinner from top to bottom.

2. The method for preparing a high modulus strength plasticity matching graphite / graphene reinforced magnesium-based composite material according to claim 1, characterized in that The drying temperature in step 1 is 80°C.

3. The method for preparing a high modulus strength plasticity matching graphite / graphene reinforced magnesium-based composite material according to claim 1, characterized in that The mass ratio of graphene, graphite and zinc powder described in step 1 is 7:3:

3.

4. The method for preparing a high modulus strength-plasticity matched graphite / graphene reinforced magnesium-based composite material according to claim 1, characterized in that The preheating temperature of the graphite / graphene predispersion prepared in step 1 described in step 2 is 200° C. and it is preheated while wrapped in aluminum foil.

5. The method for preparing a high modulus strength plasticity matching graphite / graphene reinforced magnesium-based composite material according to claim 1, characterized in that The gradient homogenization heat treatment described in step three is: first keep the temperature at 350°C to 360°C for 6 hours, then increase the temperature to 400°C to 410°C and keep the temperature for 14 hours, and finally perform rapid water cooling.